Thanku : poems of gratitude - Bruchac, Joseph, 1942- (Millbrook Press, 2019)
This poetry anthology, edited by Miranda Paul, explores a wide range of ways to be grateful (from gratitude for a puppy to gratitude for family to gratitude for the sky) with poems by a diverse group of contributors, including Joseph Bruchac, Margarita Engle, Cynthia Leitich Smith, Naomi Shihab Nye, Charles Waters, and Jane Yolen.